Role of Recent Therapeutic Applications and the Infection Strategies of Shiga Toxin-Producing Escherichia coli - Hwang, Su-bin; Chelliah, Ramachandran; Kang, Ji Eun; Rubab, Momna; Banan-MwineDaliri, Eric; Elahi, Fazle; Oh, Deog-Hwan (Frontiers in Cellular and Infection Microbiology, 2021)
Shiga toxin-producing Escherichia coli (STEC) is a global foodborne bacterial pathogen that is often accountable for colon disorder or distress. STEC commonly induces severe diarrhea in hosts but can cause critical illnesses due to the Shiga toxin virulence factors. To date, there have been a significant number of STEC serotypes have been evolved. STECs vary from nausea and hemorrhoid (HC) to possible lethal hemolytic-based uremic syndrome (HUS), thrombotic thrombocytopenic purpura (TTP). Inflammation-based STEC is usually a foodborne illness with Shiga toxins (Stx 1 and 2) thought to be pathogenesis. The STEC’s pathogenicity depends significantly on developing one or more Shiga toxins, which can constrain host cell protein synthesis leading to cytotoxicity. In managing STEC infections, antimicrobial agents are generally avoided, as bacterial damage and discharge of accumulated toxins are thought the body. It has also been documented that certain antibiotics improve toxin production and the development of these species. Many different groups have attempted various therapies, including toxin-focused antibodies, toxin-based polymers, synbiotic agents, and secondary metabolites remedies. Besides, in recent years, antibiotics’ efficacy in treating STEC infections has been reassessed with some encouraging methods. Nevertheless, the primary role of synbiotic effectiveness (probiotic and prebiotic) against pathogenic STEC and other enteropathogens is less recognized. Additional studies are required to understand the mechanisms of action of probiotic bacteria and yeast against STEC infection. Because of the consensus contraindication of antimicrobials for these bacterial pathogens, the examination was focused on alternative remedy strategies for STEC infections. The rise of novel STEC serotypes and approaches employed in its treatment are highlighted.